Analysis of e-banking activity from the sample point of view of commercial bank managers in Erbil city / 2018 - Yaseen Othman Abdullah; Luqman Othman Omar; Kochar Mohammad Abdullah (Zanco Journal of Humanity Sciences)
The banking industry has witnessed a significant expansion in banking technology in recent decades; one of the most popular aspects of it, is electronic banking, which is differs from traditional banks because of its features. The research aims to identify the importance and advantages of electronic banking, in addition, the obstacles those face its spread in the Erbil city in order to do its commercial activities electronically. Therefore, this paper has concluded with a number of points:  The electronic channels those used in the commercial banks of the study’s sample are ATM, phone banking, messaging and instant bank, as well as internet bank, add to The electronic channels in commercial banks are an easy way to enter the local and international markets. In addition, it is a positive power point to develop the electronic commercial, as well as Electronic banking faces with many obstacles, such as the lacks of laws encourage banks to adopt electronic banking and the lack of trained employees as well as the lack of technological infrastructure. The research, also, has reached to a number of recommendations, such as: To strength the infrastructure of the banking system by increasing the investment spending in information technology field and expanding the use of the network to provide variety of modern services to customers with higher efficiency and lower cost, add to Legislating laws to control electronic banking transactions, especially those related to relationship between the bank and the customer and determining the rights and duties of each party. And, the central bank could be powers point to execute those laws, as well as Prepare a plan for the training of human resources in a wide, continuous and parallel with the rapid developments in electronic systems and enhance the efficiency of human cadres for dealing with the electronic banking system.